2019
DOI: 10.1111/nmo.13585
|View full text |Cite
|
Sign up to set email alerts
|

Effects of ginger constituent 6‐shogaol on gastroesophageal vagal afferent C‐fibers

Abstract: Background Ginger has been used as an herbal medicine worldwide to relieve nausea/vomiting and gastrointestinal discomfort, but the cellular and molecular mechanisms of its neuronal action remain unclear. The present study aimed to determine the effects of ginger constituent 6‐shogaol on gastroesophageal vagal nodose C‐fibers. Methods Extracellular single‐unit recording and two‐photon nodose neuron imaging were performed, respectively, in ex vivo gastroesophageal‐vagal preparations from wild type and Pirt‐GCaM… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
11
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
5
1
1

Relationship

1
6

Authors

Journals

citations
Cited by 8 publications
(11 citation statements)
references
References 28 publications
0
11
0
Order By: Relevance
“…Thus, in PPPD patients, HBT is hypothesized to have an anti-diuretic effect in the inner ear, consistent with strategy 1, while CREB-BDNF activation in the hippocampus, cerebral cortex, and vestibular nucleus has the same action as SSRIs/SSNIs, which has therapeutic effects in PPPD[ 55 , 69 ], and is consistent with strategies 2 and 3. In addition, gastroesophageal vagal nerve activation by HBT[ 58 , 70 ] might produce feedback resulting in somatosensory suppression via the autonomic nervous system in the hypothalamus, anterior cingulate gyrus, and insular cortex[ 71 , 72 ], resulting in sensory reweighting to establish a balance between the systems and increased tolerance to the perceived stimulus ( i.e. , strategies 2 and 3).…”
Section: Discussionmentioning
confidence: 99%
“…Thus, in PPPD patients, HBT is hypothesized to have an anti-diuretic effect in the inner ear, consistent with strategy 1, while CREB-BDNF activation in the hippocampus, cerebral cortex, and vestibular nucleus has the same action as SSRIs/SSNIs, which has therapeutic effects in PPPD[ 55 , 69 ], and is consistent with strategies 2 and 3. In addition, gastroesophageal vagal nerve activation by HBT[ 58 , 70 ] might produce feedback resulting in somatosensory suppression via the autonomic nervous system in the hypothalamus, anterior cingulate gyrus, and insular cortex[ 71 , 72 ], resulting in sensory reweighting to establish a balance between the systems and increased tolerance to the perceived stimulus ( i.e. , strategies 2 and 3).…”
Section: Discussionmentioning
confidence: 99%
“…41 More recently, it was shown that the antiemetic effect of ginger may be TA B L E 3 Incidence of the primary outcome in the ginger and placebo arms partly dependent upon its modulating effect on the vagal nociceptive receptors of the gastrointestinal tract. 42 In conclusion, we found that ginger is effective at reducing vomiting in children with AGE. Further clinical trials are warranted to confirm our findings, to define the most effective dose of ginger, and to test whether ginger could be effective at improving vomiting of different etiologies in childhood.…”
Section: Discussionmentioning
confidence: 59%
“…An attractive appeal of herbal medicines is the prospect to target simultaneously multiple putative pathophysiological mechanisms. Herbal medicines frequently comprise a combination of herbs with multiple reported effects on gastrointestinal motility, secretory functions, and cytoprotective and even psychotropic properties 23,28–31 . Cremonini (2014) had described the multiple putative therapeutic properties relevant to gastric functions for peppermint oil, artichoke leaf extract, STW‐5, and Rikkunshito 28 .…”
Section: Potential Of Herbal Medicines In Fd—preclinical and Clinicalmentioning
confidence: 99%